Customer Response towards Smart Phones Purchase: Verification from Structural Equation Modeling - Shrestha, Sajeeb Kumar (Tribhuvan University Journal, 2017)
This research attempts to examine the customer response towards smart phone purchase in the Nepalese context. The aim of the study was to measure the important factors that affect to consumer purchase intention, brand extension attitude and pay premium price. Descriptive and causal research design was applied in this research. Structured questionnaires were administered for validating the measurement model and testing the structural model for customer response dimensions. It was found brand name, marketing activities, and subjective norms are the most influential factors for customer response of smart phones for purchase intention, brand extension attitude and premium price.